Biocontrol potential of fluorescent pseudomonads on Rhizoctonia root rot disease caused by Rhizoctonia solani on chilli - Muda, Rul Hajar; Ahmad, Khairulmazmi; Ng, Lee Chuen (2016)
The biocontrol potential of fluorescent pseudomonads isolated from soil rhizosphere of chilli was evaluated against Rhizoctonia solani in causing root rot disease on chilli. A total of 50 isolates out of 115 potential fluorescent pseudomonads were selected based on its percentage inhibition radial growth (PIRG) for more than 65% from dual culture assay. All 50 isolates were further screened for production of volatile organic compound, hydrogen cyanide, phosphate solubilization and indole acetic acid. Forty isolates were selected based on their in vitro screenings results using hierarchical cluster analysis in IBM SPSS Statistics 20. Only 34 isolates were identified as Pseudomonas spp. using 16s rRNA sequencing. The identified species are Pseudomonas aeruginosa, Pseudomonas alcaligenes, Pseudomonas balearica, Pseudomonas monteilli, Pseudomonas mosselii, Pseudomonas putida and Pseudomonas stutzeri. A total of 13 most potential Pseudomonas spp. were further tested for seedlings vigor index. Pseudomonas putida strain SKPf10 (isolate B5C1), Pseudomonas aeruginosa strain IBBPo16 (isolate B3C56) and Pseudomonas putida strain KB9 (isolate B5C7) were selected with the most prominent in promoting plumule and radicle growth and significantly higher than the control at p < 0.05. The bio-efficacy of these fluorescent Pseudomonas spp. will be evaluated in glasshouse conditions in suppression of R. solani and enhancing plant growth of chilli seedlings.